Perbandingan Administrasi Persyaratan Kepemilikan Kendaraan Di Indonesia Dan Singapura - Simanjuntak, Poibe Gloria; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Abstract Vehicle ownership is a significant indicator for measuring the welfare and economic progress of a region. This study compares the administrative requirements for vehicle ownership in Indonesia and Singapore, two Southeast Asian island nations with differing economic backgrounds. The objective of the research is to understand the differences in vehicle ownership policies and requirements between the two countries. The method used is qualitative research with a comparative study approach, involving data analysis from relevant literature. The findings reveal that Indonesia implements basic administrative requirements such as ID cards, driving licenses, vehicle registration certificates, and vehicle ownership books with progressive annual taxes, while Singapore adopts a stricter system with high costs such as the Certificate of Entitlement (COE) and Open Vehicle Inspection (OVI), along with stringent restrictions on the growth of private vehicles. These differences reflect divergent strategies in managing vehicle ownership and addressing traffic congestion and environmental impacts in each country.